What should be the laboratory approach against isolated prolongation of a activated partial thromboplastin time? - Falay, Mesude; Senes, Mehmet; Yücel, Dogan; Turhan, Turan; Dagdaş, Simten; Pekin, Melike; Nazaroglu, Namik K.; Özet, Gülsüm (Journal of clinical laboratory analysis, 2018)
Background This study is a retrospective evaluation of patients who were subject to mixing study in our laboratory due to prolonged APTT. The preliminary diagnoses, clinical manifestations, and results of additional ordered tests were reviewed. The study aims to investigate whether repeating APTT test with a different assay prior to performing mixed study in patients with prolonged APTT would be a better alternative algorithmic approach in order to save both time and costs. Methods We retrospectively evaluated 166 patients (65 females and 101 males) who were subject to mixing study due to isolated prolonged APTT. Additional ordered tests to identify the etiology and clinical findings were reviewed. All patients who had prolonged APTT as a result of testing with Hemosil Synthasil APTT reagent in ACL TOP analyzer were repeated with Stago Cephascreen APTT reagent in STA‐R coagulation analyzer. Results APTT test was requested preoperatively in 72.2% of cases. Only 6.6% of the cases had history of bleeding. Correction with mixing study was achieved in 122 (73.5%) cases, among which 75 (45%) cases were found to have APTT test results within reference range when tested with Cephascreen reagent. In 44 (26.5%) cases, mixing study did not result in correction. Only 4 cases were confirmed to have lupus anticoagulants (LA), while 4 cases were diagnosed with hemophilia with inhibitors. Conclusion Prolonged APTT results should always be retested using a different assay prior to mixing study. The clinician and the laboratory specialist should collaborate at the postanalytical phase.